KOMITMEN ORGANISASI, KEPEMIMPINAN DAN KINERJA PADA KARYAWAN PT. PAL INDONESIA (PERSERO) - Livada Permasadari Tarjono; Gartinia Nurcholis; Widjajaning Budi (Fakultas Psikologi Universitas Hang Tuah, 2021)
Employees are the most important aspect to realize the vision and mission set by the company. One way to deal with it is to improve the performance of its employees. The purpose of this study was to determine the effect of organizational commitment and leadership on the performance of PT. PAL Indonesia (Persero). Respondents in this study amounted to 65 employees, who were selected using a non-random sample sampling technique. The results showed that there was a simultaneous influence of organizational commitment and leadership variables on employee performance variables, with a magnitude of influence of 41.8%.